Análise de minerais pesados de depósitos cretáceos, centro-leste da bacia do Grajaú, Maranhão - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2000)
The stratigraphy of Cretaceous and Tertiary deposits of the Grajaú Basin has been problematic. However, faciologic and stratigraphic studies have led to the separation of Aptian deposits (Codó and Grajaú Formations) from those formed in the middle to upper Albian and upper Cretaceous to lower Tertiary, the latter tentatively correlable to the deposits referred to the Alcântara and Cujupe Formations in the São Luís Basin. The petrographic analysis of heavy minerals has contributed to reinforce the stratigraphic model proposed for that area, whose preliminary results showed distinct assemblages distributed according to the several stratigraphic levels. In continuation of this work, the present research aimed to extend the characterization of the heavy mineral assemblages of Cretaceous deposits exposed in the central-eastern border of the Grajaú Basin, using analytical parameters that contributed to a more detailed characterization of the source rock. The results obtained indicate that the Codó Formation deposits have zircon and tourmaline as common minerals, and garnet, staurolite, rutile, anatase, epidote and apatite were rare minerals. The Alcântara Formation deposits have zircon, tourmaline and garnet as common minerals, and staurolite, rutile, anatase, epidote, apatite, cyanite, andalusite, chlorite, zoizite, sillimanite and biotite as rare to trace minerals. Samples from the Cujupe Formation show zircon and tourmaline as abundant minerals, staurolite, rutile, anatase, chlorite and epidote as trace minerals. One can suggest medium-grade metamorphic and felsic igneous rocks as the source. Although there was no source rock distinction, the mineralogical concentration varied according to stratigraphic levels, although its cause still needs to be better studied.
Heavy mineral analysis of Cretaceous deposits, central-eastern Grajaú basin, Maranhão
Keywords: Cretáceos; Minerais; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA